2021
DOI: 10.3389/fmolb.2021.664416
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Active Components and Molecular Mechanism of Tripterygium wilfordii in the Treatment of Diabetic Nephropathy

Abstract: We aimed to explore the active ingredients and molecular mechanism of Tripterygium wilfordii (TW) in the treatment of diabetic nephropathy (DN) through network pharmacology and molecular biology. First, the active ingredients and potential targets of TW were obtained through the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and related literature materials, and Cytoscape 3.7.2 software was used to construct the active ingredient-target network diagram of TW. Second, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 156 publications
(176 reference statements)
0
13
0
Order By: Relevance
“…Protein Data Bank (PDB, http://www.rcsb.org ) was used for downloading the target proteins. The protein structure and active components were modified by AutoDockTools [ 20 , 21 ]. The processed protein and DEGs were introduced into AutoDock Vina for molecular docking.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Data Bank (PDB, http://www.rcsb.org ) was used for downloading the target proteins. The protein structure and active components were modified by AutoDockTools [ 20 , 21 ]. The processed protein and DEGs were introduced into AutoDock Vina for molecular docking.…”
Section: Methodsmentioning
confidence: 99%
“…Ten studies ( Zhang et al, 2010 ; Du and Gao, 2011 ; Shen et al, 2011 ; Xu et al, 2016 ; Shi, 2018 ; Zhu et al, 2018 ; Ge et al, 2020 ; Wang et al, 2021b ; Su, 2021 ; Yang, 2021 ), comprising 944 patients, talked of Scr as an outcome. Because of high heterogeneity (I 2 = 99%), a random-effect structure was utilized, and the result showed that levels of Scr in the combination group were significantly decreased compared with AM [MD = -15.29; 95%CI: (-28.69, -1.88); p = 0.03] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies ( Zhang et al, 2010 ; Du and Gao, 2011 ; Xu et al, 2016 ; Shi, 2018 ; Ge et al, 2020 ; Wang et al, 2021b ; Su, 2021 ; Yang, 2021 ) contributed to this analysis, and 674 patients were included. The data were analyzed by a random-effect structure because the heterogeneity was high (I 2 = 83%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations